2021
DOI: 10.14202/vetworld.2021.2941-2946
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the usage (frequency and pattern) of antibiotics at the University of Maiduguri Veterinary Teaching Hospital, Maiduguri, Borno State, Nigeria

Abstract: Background and Aim: Veterinary antibiotics are widely used to treat bacterial diseases in various species of animals. However, despite the importance of these chemotherapeutic agents, their indiscriminate or extensive use can pose dangers to the animals or humans that consume edible tissues from animals contaminated with antibiotic residues. Therefore, concerns regarding their appropriate and judicious use in animals are of public health significance. This is because of the tendencies of developing resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…According to Geidam et al (2012) oxytetracycline (36.5%) was the most used and marketed antibiotic by poultry farmers in Maiduguri. Daniel et al (2021) also reported that oxytetracycline was used by 78.7% of the clinicians in University of Maiduguri, Veterinary Teaching Hospital (UMVTH). Aliyu et al (2018) also reported that oxytetracycline is used by 99.2% of veterinarians and para veterinarians in Niger State.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Geidam et al (2012) oxytetracycline (36.5%) was the most used and marketed antibiotic by poultry farmers in Maiduguri. Daniel et al (2021) also reported that oxytetracycline was used by 78.7% of the clinicians in University of Maiduguri, Veterinary Teaching Hospital (UMVTH). Aliyu et al (2018) also reported that oxytetracycline is used by 99.2% of veterinarians and para veterinarians in Niger State.…”
Section: Discussionmentioning
confidence: 99%
“…Aliyu et al (2018) also reported that oxytetracycline is used by 99.2% of veterinarians and para veterinarians in Niger State. The high percentage of usage of oxytetracycline may not be unconnected to its broad spectrum of activity, low cost and availability (Daniel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%